2, 7-Dichlorofluorescein Hydrazide as a New Fluorescent Probe for Mercury Quantification: Application to Industrial Effluents and Polluted Water Samples. (7th November 2012) - Kempahanumakkagari, Sureshkumar; Malingappa, Pandurangappa; Ambikapathi, Gopi; Kuramkote Shivanna, Devaraju
Abstract : A new fluorescent probe 2, 7-dichlorofluorescein hydrazide for mercury quantification in aqueous medium has been described. It is based on the spirolactam ring opening of colorless and nonfluorescent 2, 7-dichlorofluorescein hydrazide induced by Hg 2+ ions through the hydrolytic cleavage of amide bond to produce green-colored highly fluorescent dichlorofluorescein in alkaline medium. The significant color change of this reagent in the presence of mercury ions can be used as a sensitive naked-eye detector. The working range, limit of detection, and relative standard deviations were found to be 0.2–20 ngmL −1, 0.042 ngmL −1, and 0.69% respectively. The proposed method is free from most of the common interfering ions present in the environmental samples. The developed method has been successfully applied to determine trace level mercury from water, soil, and industrial effluents.